Dropout from a maternal and newborn continuum of care after antenatal care booking and its associated factors in Debre Berhan town, northeast Ethiopia - Tadese, Mesfin; Tessema, Saba Desta; Aklilu, Dawit; Wake, Getu Engida; Mulu, Getaneh Baye (Frontiers in Medicine, 2022)
Background: Continuum of care (CoC) is the continuity of care beginning from pregnancy to the postnatal period to improve maternal, neonatal, and child health. Dropout from the maternal CoC remains a public health challenge in Ethiopia. There are limited studies of the woman who dropped out from CoC. In addition, the available studies focused on the time dimension of the CoC and there is a paucity of data regarding the place dimension of CoC. Thus, the study aimed to determine the prevalence of dropout from maternal CoC and its associated factors in Debre Berhan town, Northeast Ethiopia. Method: A community-based cross-sectional study design was conducted among 842 mothers from September to October 2020. A cluster sampling technique was applied and data was collected through face-to-face interviews using a structured and pre-tested questionnaire. Data were cleaned and entered into Epi-Data version 4.6 and exported to SPSS version 25 for analysis. Descriptive statistics, bivariable and multivariable logistic regression analysis were run to summarize the findings and a p-value of <.05 was considered statistically significant. Result: The overall prevalence of dropout from the maternity continuum of care was 69.1%, 95% CI (66.0–72.3). The prevalence of dropout from ANC visits, skilled birth attendants, and PNC visits was 45.4%, 0.5%, and 48.7%, respectively. Rural residents, partners' level of education, monthly income, the timing of first ANC, antenatal counseling about a continuum of care, and level of satisfaction with the service delivery were significant associates of ANC dropout. Maternal age and occupation, partner’s age, media exposure, parity, the timing of first ANC, place of ANC visit, and time spent to attend ANC were significantly associated with dropout from PNC visit. Husband occupation, monthly income, number of alive children, the timing of first ANC, and time spent for ANC visit had a statistically significant association with dropout from the maternity CoC. Conclusion: Dropout from the CoC in the study area was high. Socio-economic development, partner involvement, antenatal counseling, efficient service delivery, and media exposure are vital to improving the high dropout rate from the maternal continuum of care. Keywords: Dropout, Continuum of Care, Maternal, Newborn, Factors